Faktor Faktor Yang Mempengaruhi MinatMahasiswa Menggunakan E-Wallet Dalam Mengadopsi Perkembangan Financial Technologi - Ni Luh Widya Pebriantari; I Putu Fery Karyada; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2023)
The ever-accelerating technological development will shape people's more pragmatic patterns of life. Beginning with social activities, many changes have occurred in people's life patterns, and payment methods have evolved. In the current development, Indonesia knows the term fintech (financial technology). Fintech introduces digital payment methods, or online payments, in hopes of achieving financial inclusion. Current observations examine relationships between factors that may lead to increased interest in using e-wallets among students in adopting financial technology developments (Faculty of Economics and Tourism, Hindu University, Indonesia) empirical study on students of In this observation, all active students of the Accounting Studies Program at the Faculty of Economics, Business and Tourism of the Hindu University of Indonesia from 2020 to 2022 were used as a research population with a total sample of 332 people. In the process of observation, the factors that made the students of the Faculty of Economics, Business and Tourism of Hindu University, Indonesia interested in using e-wallets were financial literacy, social influence, hedonic motivation, habits, and perceived benefits. , and perceived comfort